Hubungan usia menarche, paritas, dan penggunaan kontrasepsi oral dengan usia menapouse di desa tanjung tebat kecamatan lahat selatan kabupaten lahat - Sri Wahyuni; Siti Aisyah; Satra Yunola (Jurnal Kesehatan Saelmakers PERDANA, 2023)
World Health Organization (WHO), in 2014, the number of women all around the world who will enter menopause time in range age more than 50 estimated reach 1,2 million. Around 80% from developing countries and each year the population of women increase to 3%. The method used in this study was analytic survey with cross sectional approach. The statistical test was chi-square test. The population of this study was all menopause women at Tanjung Tebat Village, South Lahat District 2021 with total number of 96 respondents and the sample was the total of population. The univariate analysis showed that of 96 respondents studied, there was 24 respondents (25,0%) had quick menopause age, whose with slow menarche age was 37 respondents (38,5%), whose with low risk parity was 69 respondents (71,9%), and whose did not use oral contraception was 25 respondents (26,0%). The result showed that there was significant relationship between menarche age and menopause age p.value 0,002 < ? = 0,05, there was no significant relationship between parity and menopause age p.value = 0,359 < ? = 0,05, and there was significant relationship between the use of oral contraception and menopause age p.value = 0,022 < ? = 0,05. The results of this study are expected to decrease the inconvenience that might be happen when women getting menopause.